Why Teach Current Events? (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Current events should be taught in the classroom, and there are more reasons why they should than why they should not. The manuscript the reader is about to read will discuss these various reasons why current events should be taught, but will also have an honest discussion about why summative standardized testing may stand in the way of this incorporation. Through research and studies regarding social media and it's place in the world today, the manuscript will explore how these statistics show the increasing amount of news media that students interact with, and how current events can help students: stay informed, identify fake news, and help them become overall "effective citizens" which is the mission of the National Council for the Social Studies (NCSS).